LINER REGRESSION ANALYSIS IN FORECASTING HYDROPONIC PLANT NUTRIENT NEEDS - Agni Isador Harsapranata; Danny Manongga; Sutarto Wijono (INFOKUM, 2022)
The need for nutrients to support plant growth is very important, coupled with hydroponic technology, the use of nutrients is the main requirement in supporting good plant growth. Therefore, in this study the authors forecast the nutritional needs to support plant growth from time to time. The analysis used by the author is using linear regression analysis. So by using linear regression analysis, it can be known the nutritional needs in hydroponic plant growth. In determining the provision of nutrients, it is influenced by the pH of the nutrients, the height of the nutrient liquid in the reservoir, and the dissolved nutrient particles in the reservoir. Calculations are made every 4 days, within 56 days, with the type of hydroponic plant is paprika. Forecasting of nutrition is used in an Internet of Things ecosystem, so that nutrition can run automatically based on Linear Regression calculations. Forecasting in this study uses linear regression with the RMSE (Root mean square error) result of 51.47887, from these results it can be categorized as forecasting that is close to the real value